In vitro interaction of isavuconazole and anidulafungin against azole-susceptible and azole-resistant Aspergillus fumigatus isolates. (9th June 2020) - Buil, J B; Brüggemann, R J M; Bedin Denardi, L; Melchers, W J G; Verweij, P E
Abstract: Background: The voriconazole and echinocandin combination has been found to be synergistic in vitro and in vivo against most Aspergillus fumigatus isolates, both with a WT azole phenotype and an azole-resistant phenotype. The interaction between isavuconazole and echinocandins is less well studied. This is especially true for azole-resistant isolates. Objectives: We investigated the in vitro interaction between isavuconazole and anidulafungin for 30 A. fumigatus isolates including 18 azole-resistant isolates with various isavuconazole resistance phenotypes. Methods: The isavuconazole/anidulafungin interaction was studied by using an adapted EUCAST-based 2D (12 × 8) chequerboard broth microdilution colorimetric assay using XTT. The interaction was analysed by FIC index (FICi) analysis and Bliss independence (BI) interaction analysis. Results: Both the FICi analysis and the BI analysis showed synergistic interaction between isavuconazole and anidulafungin for the majority of WT and azole-resistant isolates. As we did not see significant beneficial effects of combination therapy in TR46 /Y121F/T289A isolates at clinically achievable drug concentrations, it is unlikely that TR46 /Y121F/T289A infections would benefit from isavuconazole and anidulafungin combination therapy. Conclusions: In regions with high azole resistance rates this combination may benefit patients with WT disease, azole-resistant invasive aspergillosis and those with mixed azole-susceptible and azole-resistant infection, but may not be beneficial for aspergillosis due to isolates with high isavuconazole resistance, such as TR46 /Y121F/T289A isolates.